(untitled) (Research, Society and Development, 2022)
Studies on wind direction and speed seek to portray the spatial and temporal distribution of winds in Brazilian regions, especially in areas of great socio-environmental interest, such as forests, especially the Amazon rainforest. The objective of the work was to characterize the wind flow like direction, speed and frequency of the air above a canopy at 56 m in height. Greater knowledge of the flow characteristics over the Flona Caxiuanã may lead to the elaboration of better local weather forecasts, in relation to the occurrence and intensity of precipitation, an estimate of maximum and minimum temperatures, alerts for adverse events to society such as strong winds, fires and risks in river transport. The annual speed averages were 1.83 and 1.86 m.s-1, respectively. As for the classification, there is clearly a higher frequency in relation to light winds for the years 2015 and 2016, with 54.57 and 56.50% respectively. Measured at 64 m in height at km 67 in Flona Tapajós obtained a class interval ranging from 2 to 3 m.s-1 with a frequency of 52.7%. As for the annual distribution, there is a clear predominance of winds from NE and L (together they represent 45.45% of the catchment of trade winds)for 2015, and 65.97% for 2016. During the years 2000 to 2004 , the values were statistically equal p> 0.05, with 1.60 and 1.77 ms-1 for the rainy and dry periods, respectively, and maximum of 1.79 ms-1. The wind direction was predominantly NE and L during the years evaluated, in agreement with most studies located in the study region to the detriment of the confluence of the trade winds, although with its intensity reduced in relation to normal years. The intensity of the winds did not show statistical difference when compared by seasonality, presenting few variations in relation to the direction.